Injury-Related Production of Cysteinyl Leukotrienes Contributes to Brain Damage following Experimental Traumatic Brain Injury - Farias, Santiago (Mary Ann Liebert, Inc., 2009)
The leukotrienes belong to a family of biologically active lipids derived from arachidonate that are often involved in inflammatory responses. In the central nervous system, a group of leukotrienes, known as the cysteinyl leukotrienes, is generated in brain tissue in response to a variety of acute brain injuries. Although the exact clinical significance of this excess production remains unclear, the cysteinyl leukotrienes may contribute to injury-related disruption of the brain-blood barrier and exacerbate secondary injury processes. In the present study, the formation and role of cysteinyl leukotrienes was explored in the fluid percussion injury model of traumatic brain injury in rats. The results showed that levels of the cysteinyl leukotrienes were elevated after fluid percussion injury with a maximal formation 1 hour after the injury. Neutrophils contributed to cysteinyl leukotriene formation in the injured brain hemisphere, potentially through a transcellular biosynthetic mechanism. Furthermore, pharmacological reduction of cysteinyl leukotriene formation after the injury, using MK-886, resulted in reduction of brain lesion volumes, suggesting that the cysteinyl leukotrienes play an important role in traumatic brain injury.